Isolation and molecular cloning of genes from Myrciaria dubia “camu-camu” with potential use for biotechnological production of vitamin C - Castro Gómez, Juan Carlos; Cobos Ruiz, Marianela; Maddox, J. Dylan; Imán Correa, Sixto Alfredo; Marapara del Aguila, Jorge Luis (Society for Biology and Biotechnology, 2018)
Myrciaria dubia “camu-camu” is a rich source of several bioactive phytochemicals and vitamin C (L-ascorbic acid, AsA). To gain insights about the genes involved in AsA biosynthesis in this plant species and consequently with potential use for its biotechnological production, here we report the isolation and molecular cloning of partial gene sequences of the D-mannose/L-galactose pathway. Degenerate primers designed by the multiple sequence alignment of related plant species were used to isolate in M. dubia the partial sequences of the six D-mannose/L-galactose pathway genes (GMP, GME, GGP, GPP, GDH and GLDH). The deduced protein sequences of the six genes have more than 81% sequence identity to rosids and asterids species, with a closer phylogenetic relationship to Eucalyptus grandis. In conclusion, gene sequences of the D-mannose/L-galactose pathway involved in AsA biosynthesis of M. dubia were successfully isolated and cloned and the phylogenetic analysis indicated that these genes have been relatively well conserved throughout of plant evolution, reflecting the importance of the enzymes of this metabolic pathway for plant growth and survival. Additionally, the isolation and cloning of these genes allow us to implement systems for biotechnological production of AsA.